2008
DOI: 10.1504/ijbpim.2008.024982
|View full text |Cite
|
Sign up to set email alerts
|

How to use the innovative potential of online communities? Netnography – an unobtrusive research method to absorb the knowledge and creativity of online communities

Abstract: This article investigates how the enormous knowledge-pool of online communities can be used for new product development. Except for a few examples provided in the literature, little is known about how to best absorb the knowledge of online communities and incorporate it systematically into a company's innovation process. In this article, we introduce a modified form of the netnography method, an unobtrusive, qualitative research method, to access consumers' experiences, thoughts, unsatisfied needs and ideas fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Since it focuses on the behavior/act-rather than the individual-as the ultimate unit of analysis, the lack of social and demographic cues often associated with online data should not impede trustworthiness (i.e., validity) (Kozinets, 2002). Since its inception by Robert Kozinets in 1998, netnography has increasingly been used in studies ranging from the exploration of cross-cultural ambivalence on brides-to-be through the analysis of postings on intercultural electronic message boards (Nelson and Otnes, 2005) to the identification of new product ideas through the absorption of the knowledge and creativity found in online communities (Jawecki and Fuller, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…Since it focuses on the behavior/act-rather than the individual-as the ultimate unit of analysis, the lack of social and demographic cues often associated with online data should not impede trustworthiness (i.e., validity) (Kozinets, 2002). Since its inception by Robert Kozinets in 1998, netnography has increasingly been used in studies ranging from the exploration of cross-cultural ambivalence on brides-to-be through the analysis of postings on intercultural electronic message boards (Nelson and Otnes, 2005) to the identification of new product ideas through the absorption of the knowledge and creativity found in online communities (Jawecki and Fuller, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…Jawecki and Fuller [25], followed by Roser et al [21], identified three types of co-creation activities, i.e., direct collaboration with a firm, independent customer innovation, and joint innovation activities [22]. Viewing consumers as co-creators of value, the company utilises them as operant resources in the firm's innovation process [17], making use of their creativity, skills, and knowledge.…”
Section: Authorsmentioning
confidence: 99%
“…KM framework is developed to take advantage when carrying out tasks based on KM approach, assuming if knowledge is created, transferred, and reused because an individual performs a specific task [83]. The application of KM process to support RM process has the potential to iteratively mitigate possible risks, thereby increasing the likelihood of successful project execution [84]. As a consequence, it is important to note that organizations also prioritize the infusion of RM knowledge (creation, capture, and sharing of knowledge related to potential risks to main assets).…”
Section: Discussionmentioning
confidence: 99%